The usefulness of Wi-Fi based digital chest drainage system in the post-operative care of pneumothorax - Cho, Hyun Min; Hong, Yoon Joo; Byun, Chun Sung; Hwang, Jung Joo (Journal of Thoracic Disease; Vol 8, No 3 (March 18, 2016): Journal of Thoracic Disease, 2016)
Background: Chest drainage systems are usually composed of chest tube and underwater-seal bottle. But this conventional system may restrict patients doing exercise and give clinicians obscure data about when to remove tubes because there is no objective indicator. Recently developed digital chest drainage systems may facilitate interpretation of the grade of air leak and make it easy for clinicians to decide when to remove chest tubes. In addition, with combination of wireless internet devices, monitoring and managing of drainage system distant from the patient is possible. Methods: Sixty patients of primary pneumothorax were included in a prospective randomized study and divided into two groups. Group I (study) consisted of digital chest drainage system while in group II (control), conventional underwater-seal chest bottle system was used. Data was collected from January, 2012 to September, 2013 in Eulji University Hospital, Daejeon, Korea. Results: There was no difference in age, sex, smoking history and postoperative pain between two groups. But the average length of drainage was 2.2 days in group I and 3.1 days in group II (P